Overall morbidity after total minimally invasive keyhole oesophagectomy versus hybrid oesophagectomy (the MICkey trial): study protocol for a multicentre randomized controlled trial - Klotz, Rosa; Diener, Markus K.; Schmidt, Thomas; Hackert, Thilo; Graf, Sandra; Fuchs, Hans F.; Grimminger, Peter; Egberts, Jan-Hendrick; Gockel, Ines; van der Sluis, Pieter C.; Dörr-Harim, Colette; Klose, Christina; et al. (Trials, 2023)
Oesophageal cancer (EC) is the sixth leading cause of cancer death worldwide. Oesophageal resection is the only curative treatment option for EC which is frequently performed via an abdominal and right thoracic approach (Ivor-Lewis operation). This 2-cavity operation is associated with a high risk of major complications. To reduce postoperative morbidity, several minimally invasive techniques have been developed that can be broadly classified into either hybrid oesophagectomy (HYBRID-E) via laparoscopic/robotic abdominal and open thoracic surgery or total minimally invasive oesophagectomy (MIN-E). Both, HYBIRD-E and MIN-E, compare favourable to open oesophagectomy. However, there is still an evidence gap comparing HYBRID-E with MIN-E with regard to postoperative morbidity.